Impact of Selective Quality of Life Analysis in Patients with Local Hyperhidrosis after Sympathicus Clipping [Bedeutung der selektiven Lebensqualitätsanalyse nach Sympathikus-Clipping bei Patienten mit lokaler Hyperhidrose] - Schreiner, Waldemar; Mykoliuk, Iurii; Dudek, Wojciech; Sirbu, Horia (Zentralblatt für Chirurgie, 2019)
Introduction Hyperhidrosis (HH) is associated with physical and psychological restrictions. The treatment includes both conservative and surgical methods and aims to permanently improve the quality of life (QoL) of those affected. Endoscopic sympathetic blockade (ESB) is an established surgical therapeutic method and is considered effective when conservative treatment options fail. The aim of our study was to comprehensively analyse the QoL alteration and patient satisfaction after ESB and to identify the corresponding influencing factors. Methods From July 2008 to April 2016, 105 patients were operated for treatment-refractory HH. In all cases, an ESB was performed according to the HH form and the STS expert consensus (STS: Society of Thoracic Surgeons). QoL and hyperhidrosis status were selectively analysed pre- and postoperatively and evaluated using detailed questionnaires (a self-developed questionnaire, SF36, DLQI, Hyperhidrosis LQ (HidroQoL)). Statistical processing was performed with SPSS Statistics version 21.0.0.2 for Windows (Armonk, NY: IBM Corp.). Descriptive statistical analysis and nonparametric tests were used. Results 105 patients who underwent bilateral ESB between July 2008 and April 2016 were evaluated: 73 women (69.5%) and 31 men (29.5%) with median age of 26 years (range: 16-64 years). Of the 105 patients who underwent bilateral ESB, 12 patients had focal Hyperhidrosis palmar and axillar (12.4%), 20 had Hyperhidrosis palmo-plantar (19.0%), 47 had Hyperhidrosis palmoplantar and axillar (44.8%), 11 had Hyperhidrosis axillar (10.5%), and 14 had Hyperhidrosis facial (13.3%). HydroQoL scores showed improvement in all forms of HH. All patient groups demonstrated improvement in DLQI, while the LQ analysis of SF36 showed an improvement in social functioning and mental well-being in all forms of HH other than HA. 86.7% of patients (n = 91) were satisfied with their postoperative outcome. Compensatory sweating (CS) was observed in 76.2% of cases (n = 80), without a clear LQ impact. No significant correlation between CS and the hyperhidrosis form was found. Conclusions ESB is associated with a long-time improvement in social functioning, psychological well-being, and high patient satisfaction. The onset of CS has no clear correlation to QoL and patient satisfaction.
CRIS-Team Scopus Importer:2019-05-02
Keywords: DLQI; ESB; hyperhidrosis; quality of life; SF36; sympathetic trunk